Gendered learning/learning gender in do-it-yourself communities of practice - Dirsuweit, Teresa (My University, 2019)
In this research, I explore the learning that occurs in a case study of Do-It-Yourself (DIY) workshops for women. DIY is associated with men’s work in the traditional division of labour in the home. Many women as a result, are excluded from this field of knowledge. This research is situated in the field of feminist pedagogy. This feminist pedagogical theoretical framework is extended through an engagement with social constructionist theories of learning and everyday social practice. The learning experiences and the effects that these experiences have on the everyday life worlds of women are analysed. There is a community of practice in these workshops which is caring and engaged. The workshops provide a dialogic co-creative space where women can learn DIY in an embodied way. However, despite providing a safe space for women to do identity work and question hegemonic constructions of gender, these workshops are also spaces where dominant discourses of gender difference are reiterated. Furthermore, the intersections of gender with race and class affect the dialogic co-production of knowledge. The study highlights the importance of ongoing communities of practice to support learners who have entered a field of learning which has previously excluded them. It also emphasises the importance of constant conscious engagement with the social dynamics of learning spaces
Research report submitted to the School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters in Education